2014
DOI: 10.1127/1612-166x/2014/0065-0048
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton from natural water bodies of the Patagonian Plateau

Abstract: The Patagonian Plateau is one of the most arid regions of Argentina, where mean annual rainfall ranges between 100 and 200 mm. This region contains different types of water bodies: large artifi cial lakes, permanent natural lakes, rivers and temporary ponds. In comparison with the Andean lakes, the available information on phytoplankton from the natural water bodies of the steppe is scarcer. In general, most lakes in this region range from mesotrophic to eutrophic. Limnological regional studies have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…In most of the lakes dealt with in the present paper phytoplankton abundance was dominated by chlorococcalean and volvocalean green algae (Izaguirre & Saad 2014). In general, desmids were relatively less abundant in terms of density, except in La Herradura where a Closterium species was subdominant in the phytoplankton community.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In most of the lakes dealt with in the present paper phytoplankton abundance was dominated by chlorococcalean and volvocalean green algae (Izaguirre & Saad 2014). In general, desmids were relatively less abundant in terms of density, except in La Herradura where a Closterium species was subdominant in the phytoplankton community.…”
Section: Discussionmentioning
confidence: 85%
“…The first one mostly includes deep oligotrophic lakes of glacial origin, whereas the second one hosts different types of water bodies distributed in the arid Patagonian steppe, many of them located on the basaltic plateaux. The main environmental characteristics of these two zones were detailed in previous papers (e.g., Tell et al 2011;Izaguirre & Saad 2014). Due to remoteness of the study sites, lakes located in the Patagonian Plateau have been less investigated than those in the Andean region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, zooplankton grazing pressure on phytoplankton may be reduced by trout, with increasing nutrient recycling, promoting phytoplankton growth and potentially causing trophic cascades (Carpenter and Kitchell, ; Eby et al , ). A recent study in the Lake Strobel plateau found that stocked lakes have substantially higher levels of Cyanobacteria than fishless lakes (Izaguirre and Saad, ), indicating the occurrence of changes in the phytoplankton communities.…”
Section: Discussionmentioning
confidence: 99%
“…Basins are fed by snowmelt, with a significant inter‐annual hydrological variability, and also show a wide spectrum of water characteristics, related to the nature of the recipient sediments. Even lakes that are similar in their general configuration characteristics comprise a broad range of colour and salinity, from clear freshwater to brackish lakes (Izaguirre & Saad, ; Lancelotti, Pozzi, Yorio, & Pascual, ). Many lakes, including those larger than 3 km 2 , dry out during years of low precipitation (Lancelotti, Pascual, & Gagliardini, ).…”
Section: Study Areamentioning
confidence: 99%